2022
DOI: 10.1002/suco.202100819
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of load and corrosion on the flexural performance of recycled aggregate concrete beams

Abstract: To investigate the combined effect of load and steel corrosion on the flexural performance of recycled aggregate concrete beams, considering three types of aggregate replacement ratios (i.e., 0%, 50%, and 100%) and four levels of load (i.e., 0, 0.2, 0.4, and 0.6), 12 beams were designed for accelerated corrosion test and four-points bending test. The load was applied to beams by using a designed loading device before the accelerated corrosion test. After the accelerated corrosion test, four-point bending test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…The addition of fine RA further worsened the performance of the beams when it was incorporated in concrete 41 . In principle, the strength capacity values that are estimated in current standards are on the safe side, 39,42 although the models were extensively tested in various studies, to ensure the reliability of the calculation methods. Thus, partial factors to offset the effects of using RA on beam‐design safety have been proposed 43,44 .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fine RA further worsened the performance of the beams when it was incorporated in concrete 41 . In principle, the strength capacity values that are estimated in current standards are on the safe side, 39,42 although the models were extensively tested in various studies, to ensure the reliability of the calculation methods. Thus, partial factors to offset the effects of using RA on beam‐design safety have been proposed 43,44 .…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] To date, a number of researchers have investigated several properties of RAC with notable reviews on RAC that proved to be much more effective in terms of durability and mechanical aspects. 5,[37][38][39][40][41][42] Different studies suggested a reduction in the COS by 10%-20% with enhancement in the substitution of natural coarse aggregates (NCA) by recycled coarse aggregates (RCA). [43][44][45] Setting the cement content and water-to-cement (W/C) ratio the same, when NCA was substituted by RCA, the COS of RAC was dropped by 20%-25% in comparison to traditional concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In their test, there were three beams in each group, of which one beam was the control beam, and the other two beams were loaded (i.e., 60% of the flexural capacity), and the corrosion‐induced cracking and degradation of flexural performance of RAC beams under combined effect of load and steel corrosion were studied. Wang and Xu 30 investigated the combined effect of load and steel corrosion on the flexural performance of RAC beams, and found that both yield bending moment and ultimate bending moment of corroded RAC beams decreased with the increase of load level (i.e., the ratio of the load applied to beams to the ultimate load) and RCA replacement ratio. Wang et al 31 found that for the corroded beams with 50% RCA replacement ratio, when the load level increased from 0 to 0.6, the ultimate load and ultimate deflection reduced by 10.4% and 21.2%, respectively, whereas for the corroded beams with 100% RCA replacement ratio, the corresponding reduction of ultimate load and ultimate deflection were 8.9% and 35.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%